ANALYTICAL CLICKBAIT STRATEGIES IN NEWS HEADLINES: A CASE STUDY OF MSTAR - Siti Aishah Chu Abdullah; Azza Azreenas Azman (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2025)
In the contemporary digital landscape, clickbait strategies may drive engagement, but they can also erode the credibility of both content and media organisations. This study adopted a quantitative research methodology to examine the use of clickbait headline strategies and identify recurring patterns among online journalists. The content analysis focused on news headlines, revealing three predominant types employed by mStar on TikTok, namely celebrity-focused, intriguing, and emotive headlines. Among these, celebrity-driven headlines are most prevalent, followed by intriguing and emotive ones. While sensational or emotionally charged headlines are effective in increasing audience engagement on TikTok, they pose a challenge to journalistic integrity. Content creators must strike a careful balance between attracting readers and maintaining credibility in the fiercely competitive digital media space. To navigate this, it is crucial to evaluate how audiences perceive the influence of clickbait on the credibility and trustworthiness of journalism in the digital age.